2021
DOI: 10.1016/j.ultsonch.2021.105698
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing continuous reactive crystallization of lithium carbonate in multistage mixed suspension mixed product removal crystallizers with pulsed ultrasound

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…On the other hand, the generated micro jets have a denting effect on the crystal surface, and excessive power may even break the crystal. The breakage of crystals in solution can also cause secondary nucleation [50] , [51] . Similarly, Ruecroft et al [52] have reported that excessive ultrasonic power can easily induce secondary nucleation, causing secondary growth of crystals.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the generated micro jets have a denting effect on the crystal surface, and excessive power may even break the crystal. The breakage of crystals in solution can also cause secondary nucleation [50] , [51] . Similarly, Ruecroft et al [52] have reported that excessive ultrasonic power can easily induce secondary nucleation, causing secondary growth of crystals.…”
Section: Resultsmentioning
confidence: 99%
“…However, despite its advantages, the application of ultrasound also poses some challenges, including energy consumption and the risk of thermal effects. Pulsed ultrasound is a commonly used technique to address the aforementioned issues. Figure illustrates the influence of the duty ratio on crystallization. It is observed that the yield remained essentially unchanged when the duty cycle varied from 0.2 to 1.…”
Section: Resultsmentioning
confidence: 99%